A potential mechanism for compensation in the blue—yellow visual channel - Stringham, Nicole T.; Sabatinelli, Dean; Stringham, James M. (Frontiers in Human Neuroscience, 2013)
Due to their unique contribution to human vision, the short (S)-wavelength sensitive cones, their anatomical projections and, more recently, the cortical representation of their function, have motivated intense scientific interest. The principal study of the visual channel associated with S-cone projections has been conducted using psychophysical, neurophysiological, and ex vivo anatomical techniques, whereas more recent research on the pathway has employed functional magnetic resonance imaging (fMRI). The purpose of this manuscript is to present a perspective regarding the means by which color signals within this visual channel are processed in the brain, namely how differences in short-wavelength light transmission caused by intraocular, pre-receptoral filtration are compensated for. Recent results from fMRI and psychophysical studies indicate the existence of a frequency-dependent signal amplification mechanism whereby lower frequencies result in an amplification of S-cone signals. This finding could motivate a future research direction for determining the localization of blue – yellow color processing and neural compensation in the blue - yellow visual channel.